Software Development Website Inventaris Pada Pusat Perbelanjaan XYZ - Abdul Mun’im Taufik Nugraha; Alvian Yoga Saputra; Renny Sari Dewi (JURIKOM (Jurnal Riset Komputer), 2020)
Currently the development of information technology is developing fast and demands to create an application that can solve an existing problem but has not found a solution. In the process of knowing the amount of stock, sometimes it will be difficult if you have to check manually. The application in XYZ shopping center warehouse is based on the need for accurate and accurate information management in managing the status of goods in the warehouse. The methodology used is the waterfall method, this model describes the development of software such as the flow of a waterfall, starting analysis requirements as the beginning of the process up to coding and testing at the end of the process. This application was designed using the SDLC method, by applying the Waterfall model and built using web programming languages, namely WordPress and MySQL for data storage. The result of the application is that the system can display the status of goods and provide the latest reports needed by the car shop manager